Linked interests based collaboration between MNC-NGOs in the context of low income developing countries - Asfaw, Gezahegn (My University, 2017)
The aim of this study pertains to reveal how the – linked interests based collaboration between MNC and NGOs enhances the process of shared collaborative values creation in the context of low income developing countries. In accordance with this objective, a joint-project partnership between the Heineken/EUCORD and HUNDEE (a local NGO in Ethiopia), has been launched to optimize the performance of malt-barley value chain. The project aims to create shared collaborative values in the local market and along the value chain for the stakeholders. Based on this intent the background literature section has been reviewed the context of business based partnership between MNCs & NGOs that are seeking to address the developing countries market demand and market failure. In essence, the review section attempted to show the prevailing business opportunities, challenges and constraints that exist in the low income and developing countries in general. Then to reveal the workability of this approach, cases studies with different contexts have been reviewed in order to show the trend and its practicality in addressing the market and social problems through creating shared values. Accordingly this case study has found that – linked interests based collaboration between the MNC & NGOs enhanced the commitment and desire to work together agreeably through aligning their vision, interests & objectives. Creating an atmosphere of cooperation by minimizing their inherent differences created a competitive advantage to achieve their common vision. This has further ensured the creation of shared collaborative values – that brings positive impact to the business environment.